2021
DOI: 10.1111/vox.13211
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a community of practice to improve stem cell donor recruitment in Canada

Abstract: Background and Objectives: Communities of practice (CoPs) represent effective models to achieve quality outcomes in health care. We report the development and evaluation of a CoP to improve stem cell donor recruitment in Canada. Materials and Methods:In September 2017, we invited national stakeholders in stem cell donor recruitment to participate in a Facebook group and regular e-meetings. E-meetings involved speakers and roundtable discussion on topics related to donor recruitment. The Facebook group facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The checklists also emphasized recruitment of the most-needed donors: young males and people from a diversity of ancestral backgrounds. This supports that the checklists contributed meaningfully to the observed recruitment outcomes and error reduction, and can be deployed a part of a larger effort (including training, 38 recruitment multimedia, [35][36][37]39,40 and key messaging) to support recruiters to realize best practices and recruit needed donor demographics.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The checklists also emphasized recruitment of the most-needed donors: young males and people from a diversity of ancestral backgrounds. This supports that the checklists contributed meaningfully to the observed recruitment outcomes and error reduction, and can be deployed a part of a larger effort (including training, 38 recruitment multimedia, [35][36][37]39,40 and key messaging) to support recruiters to realize best practices and recruit needed donor demographics.…”
Section: Discussionsupporting
confidence: 63%
“…There are several limitations to this analysis. With respect to the reduction in errors and improved donor recruitment outcomes seen post-implementation of the checklists, other variables may have contributed, including improvements over time to recruiter training unrelated to the checklists; additional experience accrued by each recruitment team; development of stem cell collection diagrams 35 and high-quality multimedia resources to support donor education 6,36,37 ; and the launch of a community of practice in stem cell donor recruitment in Canada, 38 in which all Stem Cell Club donor recruiters are members. Nevertheless, data from quantitative and qualitative analysis of recruiter feedback demonstrated that the checklists were frequently used as training and memory recall tools both before and at drives, including to guide recruiters to engage with needed donor demographics, deliver the information required to secure informed consent, and error-check registration and tissue sample collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The committee shared published stories with stakeholders in donor recruitment via the Facebook group of the community of practice in stem cell donation in Canada (facebook.ca/groups/stemcellclub). 33 Recruiters shared stories as part of donor recruitment campaigns spearheaded by Stem Cell Club. Press releases including stories from Why We Swab were developed and submitted to media outlets ahead of these campaigns.…”
Section: Library Usagementioning
confidence: 99%